POTRET GAYA HIDUP HEDONISME DI KALANGAN MAHASISWA (Studi pada Mahasiswa Sosiologi FISIP Universitas Lampung) - Praja, Dauzan Deriyansyah; Damayantie, Anita (SOCIOLOGIE, 2013)
This research aims to know and explain how factors cause of hedonism, other forms ofÂ  hedonism, lifestyle and impact the hedonism lifestyle among students. This type of research uses qualitative descriptive study using a kind of primary data obtained from in-depth interviews with informants. Based on research conducted the obtained results that cause factor lifestyle hedonism on informants is intercommunication friends who is also had similar lifestyle, factor media such as the internet often offer pleasure instant, and there are also environmental factors about the insensitive actions deviate from college students, as well as the lack of control of the parents of his sons lifestyle. Forms of hedonism lifestyle seen on informants is promiscuity as out at night with go to discotheques and nightspots, as well as consuming alcohol even using drugs, consumptive as many students shopping to look fashionable and following the online gambling, and ignore college with often absent college, asked absent while absent college, and hired services workmanship their jobs lesson college on others. Hedonism impact on informants cones on three things, is a decrease in motivation and achievement students, changing patterns of life being materialistic, and change the mindset of being pragmatic and indifferent.Keywords: Portraits, lifestyle, hedonism